Unveiling Current and Future Trends in the Implementation of Teaching Games for Understanding in Primary School: A Bibliometric Analysis - Oktavianus, Irfan; Gustian, Uray; Triansyah, Andika (Physical Education Theory and Methodology, 2025)
Background. Physical Education (PE) often focuses on sports skills through command-based teaching methods, which can lead to students struggling to understand and effectively play games. To address this issue, Teaching Games for Understanding (TGfU) has been introduced as a more effective approach to enhance tactical comprehension and gameplay skills, while also increasing student engagement in physical activities. Objectives. This study aimed to identify current research trends and future potential for TGfU implementation in elementary school PE through a bibliometric analysis. Materials and methods. A bibliometric approach was used by analyzing 977 documents from the Scopus database published between 2015 and 2024. The data was analyzed using VOSviewer to map bibliographic networks and conduct keyword analysis. A science mapping approach was applied to identify emerging research trends and predict the future of TGfU implementation. Results. The analysis revealed that TGfU implementation effectively improves physical activity, motor skills, and the well-being of elementary students. However, further research is needed to fully understand and validate these findings.Current trends emphasize the importance of PE in enhancing physical activity, motor skills, and student well-being through the TGfU approach. Future trends point towards developing PE curricula that undersore the integrated use of TGfU and holistic approaches. Conclusions. Implementing TGfU in elementary schools holds great potential for improving physical engagement, tactical skill development, and students’ psychological well-being. Challenges include optimizing the role of teachers as facilitators and adapting the curriculum for broader TGfU application. Further research is required to validate the application of the TGfU model in PE curricula and to develop approaches relevant to the needs of elementary students.